Opportunities and Challenges of the Cheesy Corn Business: A Feasibility Study in Central Cikarang’s Clean Market - Pratama, Martha Putri; Naufal, Muhammad; Sembiring, Theresia Aprilia Br; Madani, Hanif Al; Rahmawati, Irma; Dianugra, Muhammad Keizhar (Lentera Ilmu Nusantara, 2025)
The purpose of this article is to discuss the Cheesy Corn business as an innovative business. Cheesy Corn products offer a combination of classic flavors and new flavor variants that differ from typical cheese corn. The research method for assessing the feasibility of the Cheesy business involves a qualitative descriptive approach through systematic stages. The data analysis technique uses triangulation, which evaluates various aspects such as the market, human resource management, operations, and finance. This research focuses on the development of the Cheesy Corn business concept as an innovative new business in the Central Cikarang area. The location of the Clean Market is a strategic consideration because it has active and diverse consumer dynamics, especially from the middle and lower middle classes who are always looking for affordable but quality snacks.